Emotion regulation as a determinant of recovery experiences and well-being: a day-level study - Schraub, Eva Maria; Turgut, Sarah; Sonntag, Karlheinz (International journal of stress management, 2013)
This study examined the impact of two emotion regulation strategies, reappraisal and expressive suppression, on recovery experiences and affective well-being after significant study-related events. In a sample of 63 undergraduate students who completed a time-contingent daily diary over 14 consecutive days (726 diary entries), the assumption that perceived emotional stress during study-related events would reduce affective well-being at bedtime (β = −0.28, p < .001) was supported. Multilevel analyses further showed that recovery experiences partially mediated this negative relationship (β = 0.39, p < .001). As postulated, reappraisal buffered the adverse effects of emotional stress on recovery experiences (β = 0.05, p < .01). Unexpectedly, expressive suppression had the same buffering effect (β = 0.04, p < .05). We conclude that an additional, fine-grained focus on context and time would usefully enhance our knowledge of the effects of emotion regulation on stress responses.
Gesehen am 19.07.2021